2012
DOI: 10.1021/bm300545b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Size, Surface Charge, and Hydrophobicity of Poly(amidoamine) Dendrimers on Their Skin Penetration

Abstract: The barrier functions of the stratum corneum (SC) and the epidermal layers present a tremendous challenge in achieving effective transdermal delivery of drug molecules. Although a few reports have shown that poly(amidoamine) (PAMAM) dendrimers are effective skin penetration enhancers, little is known regarding the fundamental mechanisms behind the dendrimer-skin interactions. In this paper, we have performed a systematic study to better elucidate how dendrimers interact with skin layers depending on their size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(111 citation statements)
references
References 32 publications
1
110
0
Order By: Relevance
“…Confocal images showed that G2-NH2 could be internalized into the individual cell in both epidermal and dermal layers, while neither acetyl nor carboxyl modified PAMAM interacted with the cell. The study also found that conjugation of oleic acid to G2-NH2 could further increase the drug absorption and retention in the skin (Yang et al, 2012).…”
Section: Dendrimersmentioning
confidence: 78%
“…Confocal images showed that G2-NH2 could be internalized into the individual cell in both epidermal and dermal layers, while neither acetyl nor carboxyl modified PAMAM interacted with the cell. The study also found that conjugation of oleic acid to G2-NH2 could further increase the drug absorption and retention in the skin (Yang et al, 2012).…”
Section: Dendrimersmentioning
confidence: 78%
“…Since properties of dendrimers depend on their size and surface charge (Malik et al 2000), lower generation of PAMAM are more preferred for examination in dermal formulations, because of their stronger ability to enhance the permeation and lower toxicity (Heiden et al, 2007;Winnicka et al, 2009). PAMAM-NH 2 in contrast to neutral and anionic dendrimers can be accumulated in the skin upper layers (Yang et al, 2012), which makes them proper carriers for topical drug delivery. The effect of PAMAM dendrimers G2 and G3 with various surface groups on the release of CLO from hydrogels with CLO in two different molecular states and from water suspensions was studied, because the size and surface charge of dendrimers can influence the permeation of the drug.…”
Section: Resultsmentioning
confidence: 99%
“…15 A recent study with poly (amidoamine) (PAMAM) dendrimers conjugated with rhodamine B isothiocyanate reported penetration in porcine skin. 21 The authors used a Zeiss LSM 510 Meta confocal laser scanning microscope with a 1 mW helium-neon laser at 543 nm to image the localization of PAMAM in the skin. They hypothesized that these dendrimers at smaller sizes can penetrate the skin layers more efficiently than the larger dendrimers.…”
Section: Np Penetration In Skin Depends On Np Physiochemical Propertiesmentioning
confidence: 99%